Environmental policy and technological innovation : why do firms adopt or reject new technologies? - Montalvo Corral, Carlos (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2002)
Environmental Policy and Technological Innovation comprehensively explores the factors which can influence a firm's behavioural approach towards developing clean technologies. Unlike many other studies on environmental policy, it addresses the origin of the problems and not just the symptoms. It will become an indispensable companion for local, national and international environmental regulators, environmental policymakers and analysts, and those interested in technological innovation and technology policy.
Includes index.
Includes bibliographical references (p. [264]-293).
rpm 22/09/16
Loans
Keywords: Environmental policy; Environmental responsibility; Business enterprises